Assessing the economic benefit of a bidding decision support tool for wind power producers. Issue 6 (1st November 2013) - Moreno, Maria Ángeles; Usaola, Julio; Bueno, Miriam
Abstract : This document describes the assessment of a decision support tool for wind power producers in real wind farms. This tool allows them to update their positions taken in daily markets into subsequent adjustment markets. The tool intends to maximise the revenues of wind power producers that participate in electricity markets through an optimisation procedure, making use of the possibilities of non‐continuous adjustment markets and the probabilistic tools developed in the EU project ANEMOS.plus. Results are presented for nine Spanish wind farms and they are compared with those obtained with a standard strategy of market participation for wind power producers. For the examined cases, the revenues were overall increased in a 1.3% by using the decision support tool. This could encourage even more the participation of wind energy in electricity markets. The overall energy imbalance also increases, showing a potential risk for the whole system if all wind power producers would use such a tool.